Deteksi Dini Hipertensi dan Obesitas pada Ibu Hamil dan Ibu Menyusui di Kasemen, Serang - Yana Aurora Prathita; Hilliza Awalina Zulfa; Louisa Ivana Utami (Universitas Pahlawan Tuanku Tambusai, 2026)
Blood pressure and anthropometry are among the examinations that can be performed in primary care and are mandatory examinations during ANC. The maternal mortality rate (MMR) in Indonesia remains high at 189 per 100,000 live births. In 2024, the MMR in Banten province will be 163 deaths per 100,000 live births, making it a priority to reduce maternal mortality in Indonesia. Approximately 14% of the cause of mortality in pregnancy is eclampsia, which is a complication of high blood pressure. This community service activity in the Kasemen area, Serang, aims to detect blood pressure, weight, and height in pregnant and breastfeeding women. The incidence of hypertension remains high, and excess weight is a dominant figure in pregnant and breastfeeding women. Education on blood pressure and excess weight control, as well as the potential impacts, especially complications of hypertension, in pregnant women should be a priority in this activity, especially during ANC visits.